Качество пломбирования корневых каналов зубов у пациентов с сердечно-сосудистыми заболеваниями (Эндодонтия Today, 2020)
The analysis of the observation of over 60 patients with systematic cardiovascular diseases indicated that the frequency of root canal filling with a single gutta-percha pin is high. Endodontic treatment of 24% of teeth of patients aged 20 to 29 years had been performed with a low quality of obturation of root canals. The quality of endodontic treatment of patients with cardiovascular diseases should always be evaluated using radiographs.